Employee Performance and Patient Retention: Service Quality as a Mediating Mechanism for Institutional Growth - Beny Irawan; Wiliyanarti, Pipit; Mochamad Mochklas; Setya Haksama (Health and Technology Journal (HTechJ), 2026)
Escalating patient volume is a critical metric of healthcare institutional efficacy, fundamentally driven by internal organizational dynamics. This study investigates the impact of employee performance on perceived patient volume growth at Qonaah Hospital, utilizing service quality as a mediating variable. A quantitative exploratory design with a cross-sectional approach was adopted. Data were synthesized from structured interviews with 100 outpatients and analyzed via multiple linear regression and the Sobel mediation test. Employee performance was operationalized through work quality and efficiency metrics, service quality was evaluated using the SERVQUAL framework, and patient volume was quantified through satisfaction and revisit intention indicators. Statistical analysis revealed that employee performance exerts a positive and significant influence on service quality (β = 0.413; p = 0.001) and perceived patient volume (β = 0.416; p < 0.001). Service quality also significantly predicts perceived patient growth (β = 0.353; p < 0.001). The Sobel test confirmed that service quality partially mediates the relationship between performance and patient volume (t = 3.135; p < 0.05). Optimizing workforce efficacy directly drives institutional growth within competitive healthcare environments. This internal operational excellence achieves maximum impact when systematically translated into tangible, patient-centered care experiences. Hospital administrators must adopt a synergistic management paradigm integrating continuous professional development with rigorous quality assurance protocols to ensure sustainable market viability.